Alpian, Yanciluk, dan Wahyu Supriyati : PEMBUATAN PELET DARI SERBUK LIMBAH KAYU MENGGUNAKAN ALAT PENGEMPA DAN CETAK SEDERHANA - Agrienvi (Agrienvi: Jurnal Ilmu Pertanian, 2019)
Energy demand increase follow to population growth factors, high exploration costs, rising world oil prices andthe difficulty of finding sources of oil reserves. These factors cause the governments of several countries toimmediately produce alternative energy that is renewable and environmentally friendly. Wood pellets are analternative energy source. The availability of raw materials is very easy to obtain. Raw materials for wood pelletsfrom the exploitation waste such as logging residues, branches and twigs, wood industry waste such as scraps,sawdust and bark, agricultural waste such as straw and husks. Waste that is developed into a product will produce ahigher economic value. Making pellets from wood waste is an alternative energy material for meeting people's energyneeds. The opportunity to develop wood pellets as fuel is wide open because of the vast potential of forests inIndonesia and the large amount of waste from forest products, both from timber industry waste and exploitationwaste. Equipment, raw materials and the process of making pellets in a simple manner need to be socialized to thepublic so that they can be applied especially for the utilization of potential waste that can be used as raw material formaking pellets.Keywords : wood pellets, waste, simple technology, renewable energy